2021
DOI: 10.1186/s12933-021-01226-5
|View full text |Cite
|
Sign up to set email alerts
|

The predictive utility of circulating PCSK9 levels on diabetes mellitus

Abstract: Increasing data including ours have suggested that proprotein convertase subtilisin/kexin type 9 (PCSK9), a novel regulator of cholesterol metabolism, may also play an important role in the development of type 2 diabetes mellitus (T2DM) and is associated with clinical outcomes in diabetic patients. Previous studies revealed that elevated plasma PCSK9 levels had a higher incidence of new-onset T2DM. Moreover, the results of available epidemiological, preclinical, and clinical studies have indicated that plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Third, although we could speculate on the neutralizing function of the PCSK9-Abs, it remains unclear. Fourth, although it has been reported that the concentration of circulating PCSK9 might be a predictor for the development of type 2 DM 31 , we could not follow up the HD population; consequently, we do not know whether their PCSK9-Ab levels will relate with the new onset of diabetes in this population.…”
Section: Discussionmentioning
confidence: 95%
“…Third, although we could speculate on the neutralizing function of the PCSK9-Abs, it remains unclear. Fourth, although it has been reported that the concentration of circulating PCSK9 might be a predictor for the development of type 2 DM 31 , we could not follow up the HD population; consequently, we do not know whether their PCSK9-Ab levels will relate with the new onset of diabetes in this population.…”
Section: Discussionmentioning
confidence: 95%
“…13 Emerging data suggest PCSK9 as a risk factor for type 2 diabetes mellitus (T2DM) with several preclinical and clinical studies indicating a role for this molecule in glycometabolic disturbances and as a predictor of CV outcome in diabetic patients with coronary artery disease (CAD). [14][15][16] Yet, reports are often conflicting and whether PCSK9 levels could work as a reliable marker of vascular stiffness in such population remains unclear. 17 The aim of the present study is to evaluate the associations between circulating PCSK9 levels and arterial stiffness assessed as carotid-femoral PWV.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data suggest PCSK9 as a risk factor for type 2 diabetes mellitus (T2DM) with several preclinical and clinical studies indicating a role for this molecule in glycometabolic disturbances and as a predictor of CV outcome in diabetic patients with coronary artery disease (CAD) 14–16 …”
Section: Introductionmentioning
confidence: 99%